Ischemia-modified albumin as an oxidative stress biomarker in early pregnancy loss. (2nd June 2016) - Cengiz, Huseyin; Dagdeviren, Hediye; Kanawati, Ammar; Suzen Çaypinar, Sema; Yesil, Ali; Ekin, Murat; Yasar, Levent
Abstract: Background/aims : This study aimed to determine the association between early pregnancy loss and serum ischemia-modified albumin (IMA) concentrations. Methods : Serum samples of 180 women that included healthy pregnant women, women admitted for termination of pregnancy due to the absence of fetal cardiac activity or absence of fetal pole on ultrasonographic examination, and healthy non-pregnant women attending for gynecological examination. Each group included 60 patients. Serum concentrations of IMA were compared among the groups, and the correlations with patients' age, gravidity, BMI, gestational age and total serum albumin concentrations were calculated. Results : When the groups were compared with respect to IMA concentrations, the group with early pregnancy loss was found to have significantly higher IMA concentrations ( p  < 0.001). An IMA threshold of >163 ng/mL had a sensitivity of 75%, specificity of 55% to discriminate between healthy pregnant patients and patients with early pregnancy loss in first trimester. Conclusion : Our findings support the theory that possible oxidative stress, a more hypoxic environment and defective placentation lead to increased serum IMA concentrations. These findings may help to shed light on the complicated pathogenesis of early pregnancy loss.